ADHD: VAGUE CONCEPTS, QUESTIONABLE EXISTENCE - Viégas, Lygia de Sousa; Felício de Oliveira, Ariane Rocha (Nuances: estudos sobre Educação, 2014)
This article aims to critically analyse the scientist discourse that defends the Attention Deficit Hyperactivity Disorder (ADHD) as a neurobiology disorder of genetic origin and, therefore, present diagnosis and treatment proposals for children that allegedly are bearer of this assumed disease. For this purpose, it gathers a set of scientific publication over the theme, mainly in the psychology and neurology field, wich are the most criticized in the light of the debate surrounding the life medicalization. It is expected with this article to fuel the debate about the medicalized education and to contribute to overcome this situation. http://dx.doi.org/10.14572/nuances.v25i1.2736